Strategi Pemasaran Tanaman Cabai Rawit (Capsicum frutescens L) di Erik Farm Desa Ladogahar Kecamatan Nita Kabupaten Sikka - Maria Susana Loda; Gabriel Otan Apelabi (Jurnal Ilmiah Wahana Pendidikan, 2022)
An efficient marketing system will drive low marketing margins so that improvements in revenue on the part of producers, relatively cheap prices for consumers and normal profits for marketers will be achieved. Chili in addition to being able to be used as a daily requirement, chili is also widely used as a raw material for the food and pharmaceutical industries. The purpose of the research is to explore the marketing strategy of cayenne pepper farming business in Erik Farm, ladogahar village, nita subdistrict, sikka district. The marketing strategy of cayenne pepper farming business in ladogahar village of Nita District of Sikka Regency is in the position of quadrant I, which is the most profitable position for farmers because at this time cayenne pepper farming business has the opportunity and strength so that it can be utilized, namely: 1) increase market demand by utilizing the labor and experience of chili farmers. 2) Take advantage of the selling price by increasing the volume of production with the proper use of fertilizers and pesticides.